ANALYSIS OF ITEMS OF SUSTAINABLE QUALITY OF LIFE CONCEPT BASED ON EXTENDED LINEAR MULTI-REGRESSION MODEL - Todorovic, Gordana; Savovic, Ivan; Djordjevic, Aleksandar M (Journal of Applied Engineering Science, 2016)
In this paper, an extended multi-regression model for determining strength relation among dimensions of sustainable development and quality of life in section of communal services in urban areas is developed. The relative importance of dimensions of sustainable development is stated by pair-wise comparison matrix. The values of dimensions of sustainable development and quality of life are assessed by decision makers. Judgments of decision makers are mapped into common measurement scale. The weighted values of sustainable development dimensions are calculated as product of their weights and assessed values. The assessed values of quality life are depended variable in the proposed linear multi-regression model. By using standard statistical software, partial correlation coefficients are given. The proposed linear multi-regression model is illustrated by example with real life data.
Keywords: Quality of Life; assessment; Sustainable development; sustainable use